Disappearance of An. minimus and An. dirus from Certain Malaria Endemic Areas of Assam, India - Kavita Yadav; Sunil Dhiman; Bipul Rabha; Diganta Goswami; PK Saikia; Vijay Veer (Tehran University of Medical Sciences, 2017)
Background: Orang Primary Health Centre (OPHC) and Balipara Primary Health Centre (BPHC) of Assam (India) report mosquito borne diseases annually. Current study was performed to ascertain the prevalence of known malaria and Japanese Encephalitis (JE) vectors and their possible role in disease transmission. Methods: Malaria epidemiological data for 2006-2010 and JE data for 2008-2013 of Assam, India were obtained from the health authority. Mosquitoes were collected using CDC light traps and identified morpho-taxonomically. Results: Plasmodium falciparum cases (81.5%, 95% CI= 72.0-91.1) were statistically higher in OPHC (P< 0.0001, t= 8.0) during the recent years. There was 4.4 folds rise in the confirmed acute encephalitis syndrome (AES) and 3.2 folds increase in the confirmed JE cases during 2013 as compared to 2008. Altogether 9,218 mosquito specimens (PTND= 153.6), comprising of 44.1% anophelines (PTND= 67.7), 42.3% culicines (PTND= 65.0) and 9.5% mansonia (PTND= 14.6) were recorded. In BPHC, An. vagus was recorded in high density (P< 0.0001), whereas Cx. quinquefasciatus was the predominant JE vector (P= 0.04). In OPHC, among the known malaria vectors, the density of An. annularis was significantly high (P< 0.0001). However Culex bitaeniorhynchus was the predominant known JE vector (P< 0.0001) followed by Cx. quinquefasciatus. Conclusion: Even in the absence of known efficient vectors, many Anopheles species are still involved in malaria transmission. There was disappearance of An. minimus and An. dirus and establishment of An. annularis, An. vagus and An. philippinensis/nivipes mosquitoes in study area.